SQ3R Method in Teaching Reading: How It Improves Students’ Comprehension of Narrative Texts at SMAN 2 Trenggalek - Wawan Prasetyo (FOSTER: Journal of English Language Teaching, 2022)
Many students think that reading skill is really difficult and complicated. Students said that finding meaning is confusing. Sometimes students misinterpret the text even if they have sufficient vocabulary. The problem in understanding the text is likely to trigger another problem in English, such as giving up easily and being lazy to continue studying their English activity. Moreover, reading is the activity most frequently done by students. They read the lesson written by their teacher on the whiteboard and from the books. Meanwhile, reading narrative text is of reading types that are mostly discussed in senior high school. In trying to solve this problem, the writer did classroom action research in his school. This research was done to improve students’ reading comprehension in the tenth-grade students of SMAN 2 Trenggalek through the SQ3R method. The data of this research was gained from the interview, observation, test, questionnaire and English score. This research was conducted in two cycles. The result of the first cycle and second cycle indicated that the number of students who passed the test is increasing significantly. Based on the result of the study, it can be concluded that the SQ3R method can improve reading comprehension skills.